Image retrieval using color histograms - Lai, Francis P. (Animo Repository, 2009)
In this paper, we describe the implementation and results of an examples based image retrieval system. Three algorithms were implemented: Normalized RGB Histogram, Euclidean Distance and the weighted histogram intersection. Results from the first 20 images of a database of 5,000 images are evaluated using the precision measure.